2023
DOI: 10.56369/tsaes.4526
|View full text |Cite
|
Sign up to set email alerts
|

INSECTOS VISITANTES FLORALES EN Bactris gasipaes Kunth (ARECACEAE) EN PANAMÁ

Abstract: <p><strong>Background. </strong>Floral visitor insects constitute part of the diversity of arthropods associated with flowers of angiosperm plants such as palms of the Arecaceae family, specifically <em>Bactris gasipaes</em> Kunth, known in Panama as pifá.<strong> Objective. </strong>Identify flower-visiting insects on inflorescences of <em>B. gasipaes</em> in Panama. <strong>Methodology. </strong>The study was carried out from March to June 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It appears that the presence of scarab beetles may be related to locality rather than species of palm. However, Atencio-Valdespino et al (2023) found a few scarabs on inflorescences of B. gasipaes in Panama. Núñez (2014) found scarab visitors to inflorescences in 40 out of 58 species of Colombian palms.…”
Section: Bactrismentioning
confidence: 97%
“…It appears that the presence of scarab beetles may be related to locality rather than species of palm. However, Atencio-Valdespino et al (2023) found a few scarabs on inflorescences of B. gasipaes in Panama. Núñez (2014) found scarab visitors to inflorescences in 40 out of 58 species of Colombian palms.…”
Section: Bactrismentioning
confidence: 97%
“…Recently, there has been an increase in studies on the reproductive biology of highly economically important palms (Bezerra et al., 2020; Guerrero & Núñez, 2017; Núñez et al., 2014; Núñez & Carreño, 2013). Most studies evaluate individual species, but few of them analyze related species (Atencio‐Valdespino et al., 2023; Núñez & Carreño, 2016b; Núñez & Rojas‐Robles, 2008). Under niche conservatism, it is reasonable to assume that related plant species have similar interactions (Cirtwill et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is little detailed information on the pollinators of the different Prestoea species, Núñez and Carreño (2016a) Recently, there has been an increase in studies on the reproductive biology of highly economically important palms (Bezerra et al, 2020;Guerrero & Núñez, 2017;Núñez et al, 2014;Núñez & Carreño, 2013). Most studies evaluate individual species, but few of them analyze related species (Atencio-Valdespino et al, 2023;Núñez & Carreño, 2016b;Núñez & Rojas-Robles, 2008).…”
mentioning
confidence: 99%